Improving Student’s Attitude of Nationalism Through Group Counselling Based on 3M Lickona (Jurnal Bimbingan Konseling, 2019)
The main goal of this research is to find out the level of effectiveness of Pshyco Educational Group Based 3M Lickona to nationalism attitude students SMP Agus Salim Semarang City. According to the research results the Pshyco Educational Group Based 3M Lickona is effective to improve students nationalism attitude.